COMPARATIVE STRUCTURAL STABILITY OF HISTONES BY INTERACTION OF SODIUM NDODECYL SULPHATE (Journal of Sciences, Islamic Republic of Iran)
The interaction of sodium n-dodecyl sulphate (SDS) with histones in phosphate buffer pH 6.4 has been studied spectroscopically and by equilibrium dialysis. The enthalpies of interaction and the spectroscopic data suggest different structural stability for histones-SDS interaction. The linear relation between enthaly and absorbtion was determined by the equation of m= , where m is the stability coefficient of histones-SDS interaction indicating the relationship of the structural stability of histones-SDS complexes.